Effects of Development Transformation on Energy Consumption in ASEAN-3: Structural Vector Autoregression Approach - Shofi Dana, Bandara; Rusdianasari, Fitri; Yocub, Johanna; Pilar, Victoria (Journal of Islamic Economics Perspectives, 2024)
Abstract The existence of economic integration and liberalization in developing countries provides an increase in population migration to achieve prosperity. Migration influences the industrial sector, which indirectly affects increasing energy consumption. This research analyzes the influence of migration, increasing population, industrial sectors, and increasing GDP, which can impact energy consumption in developing countries. Using the Structural Vector Autoregression (SVAR) analysis tool will provide an overview of the relationship between migration, population increase, industrial sector, and increase in GDP in influencing energy consumption. This research shows that population changes influence energy consumption directly and indirectly with the increase in industry.